Hydrazine Oxidation Electrocatalysis - Zagal-Moya, J; Zagal-Moya, J; Muñoz-Moena, L; Muñoz-Moena, L (American Chemical Society, 2024)
The electro-oxidation of hydrazine is important for direct hydrazine fuel cells and for fundamental understanding of electrocatalysis in the nitrogen cycle. In this Review, we discuss electrocatalysis of the hydrazine oxidation reaction (HzOR), spanning a vast range of metal surfaces, nanoparticles, atomically dispersed ions, organometallic macrocycles, and enzymes. Emphasis is given to structure-activity correlations and reactivity descriptors, including the formulation of the Zagal principle, an electrochemical corollary of the Sabatier principle. In addition, we identify overarching themes that span the different subfields of HzOR electrocatalysis, hoping to inspire cross-disciplinary research avenues. © 2024 American Chemical Society
Keywords: electrocatalysis; hydrazine; single atom catalysts; Sabatier principle; alternative fuels; nitrogencycle